Mythopoetic complex "road-sea" in Ukrainian magic and heroes-fantastic tales - Манжос, Світлана Віталіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with the mythic and poetic complex “road – sea” in Ukrainian magic, heroic and fantastic tales that represent the archaic genres of folk literature. The model of the organization of the world with the motive “road – sea” is revealed, the mythic and poetic basis of the road markers is described, the main attributes of the sea and its place and role in structuring the world are described. Some images of magic, heroic and fantastic fairy tales, their semantics are characterized and some features of evolution of the images and motives connected with water are clarified. The mythic and poetic complex “road – sea” in Ukrainian folk fairytales has coordinates which reflect the oldest ideas about the mythological model of the world. In was specified that in magic fairytales the universal semiotic world model – the dendrocentric model (in the center of Universe is the World Tree). The journey of the fairy-tale hero is based on movement, which simulates coordinates of the vertical division of the World Tree.